2010
DOI: 10.1016/j.homp.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale application of highly-diluted bacteria for Leptospirosis epidemic control

Abstract: The homeoprophylactic approach was associated with a large reduction of disease incidence and control of the epidemic. The results suggest the use of HP as a feasible tool for epidemic control, further research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 23 publications
(16 reference statements)
2
49
0
3
Order By: Relevance
“…A large scale public health intervention with prophylactic homeopathically-prepared oral doses of diluted and succussed, inactivated leptospirosis bacteria in 2.3 million people in Cuba demonstrated significant reductions in disease incidence compared with non-intervention regions during a high-risk rainy season [188]. Notably, in conventional nanomedicine research, a one-dose nanoparticle-based vaccination by nasal administration has been shown effective in an animal model of a different bacterial infection, Yesinia pestis (plague) [189].…”
Section: Resultsmentioning
confidence: 99%
“…A large scale public health intervention with prophylactic homeopathically-prepared oral doses of diluted and succussed, inactivated leptospirosis bacteria in 2.3 million people in Cuba demonstrated significant reductions in disease incidence compared with non-intervention regions during a high-risk rainy season [188]. Notably, in conventional nanomedicine research, a one-dose nanoparticle-based vaccination by nasal administration has been shown effective in an animal model of a different bacterial infection, Yesinia pestis (plague) [189].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Samarakoon et al indicates that in endemic regions the knowledge of leptospirosis prevention is adequate but does not lead to implementation of personal protective measures [40]. Prophylaxis with doxycycline (200 mg once a week) reduces morbidity and mortality during outbreaks and other homeoprophylactic measures are reported to provide preventive benefit, but will require extensive evaluation [41, 42]. There is no human vaccine available but vaccines do exist for animal reservoirs including dogs and cattle.…”
Section: Leptospirosismentioning
confidence: 99%
“…Can quantum mechanical phenomena such as quantum confinement, quantum coherence, and/or quantum entanglement be experimentally demonstrated with some very small sized homeopathically-prepared medicine NPs and their interactions with living organisms? Under what circumstances might some homeopathic nanomedicines prevent disease [155], or is their primary role in treatment of pre-existing disease?…”
Section: Experimental Questionsmentioning
confidence: 99%